Plasma Selenium Concentration and Glutathione Peroxidase Activity in Red Blood Cells of Laying Hens Fed Sodium Selenite or Zinc-L-Selenomethionine - Chantiratikul, A.; Aengwanich, W.; Chinrasri, O.; Chantiratikul, P. (International Journal of Poultry Science, 2008)
The objective of this study was to determine the effect of sodium selenite and zinc-L-selenomethionine on plasma selenium (Se) concentration and glutathione peroxidase (GSH-Px) activity in the red blood cells (RBC) of laying hens. Two hundred twenty four CP Browns aged 71 weeks were divided according to a 2x3 factorial in completely randomized design. One more group without additional Se supplementation was used as negative control. Each treatment consisted of four replicates and each replicate contained eight hens. The dietary treatments were T1: basal diet, T2, T3 and T4: basal diets added 0.3, 1.0 and 3.0 mg Se from sodium selenite/kg, respectively, T5, T6 and T7: basal diets added 0.3, 1.0 and 3.0 mg Se from zinc-L-selenomethionine/kg, respectively. The findings revealed that the plasma Se concentration of hens received supplemented zinc-L-selenomethionine diets was higher (p<0.05) than that of hens received supplemented sodium selenite diets. Plasma Se concentration statistically increased (p<0.01) with increasing Se levels. The Se sources did not dramatically alter GSH-Px activity in RBC. However, GSH-Px activity significantly increased (p<0.01) with increasing dietary selenium levels. The results in this experiment indicate that zinc-L-selenomethionine increases higher plasma Se concentration than sodium selenite, however GSH-Px activity in RBC of laying hens is not affected by Se sources.